2013
DOI: 10.1021/ic402428m
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Construction of a Coordination Zirconocene Tetrahedron

Abstract: The current study describes the first in situ synthesis and characterization of a new family of cationic coordination tetrahedra of both the V4F4 and V4E6 type, which are constructed by a new building block based on a trinuclear zirconocene moiety and the dicarboxylate or tricarboxylate anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(167 citation statements)
references
References 25 publications
4
163
0
Order By: Relevance
“…Zr‐MOPs are constructed through the slow hydrolysis of Cp 2 ZrCl 2 , which results in a trinuclear ligand‐bridged Zr‐cation polyhedron (Figure a) . Single‐crystal X‐ray crystallography results indicate that an isolated cationic zirconocene coordination tetrahedron with V 4 E 6 topology (V=vertex, E=edge), {[Cp 3 Zr 3 O−(OH) 3 ] 4 (BDC) 6 } 4+ (ZrT‐1), is formed, and Cl − acts as a counterion to balance charges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zr‐MOPs are constructed through the slow hydrolysis of Cp 2 ZrCl 2 , which results in a trinuclear ligand‐bridged Zr‐cation polyhedron (Figure a) . Single‐crystal X‐ray crystallography results indicate that an isolated cationic zirconocene coordination tetrahedron with V 4 E 6 topology (V=vertex, E=edge), {[Cp 3 Zr 3 O−(OH) 3 ] 4 (BDC) 6 } 4+ (ZrT‐1), is formed, and Cl − acts as a counterion to balance charges.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Expanding upon research into Zr-MOFs, some researchers have reported the synthesis of zirconium-basedMOPs, which are composed of trinuclearz irconium clusters and different carboxylate ligands. [14] Yuan and co-workers synthesized as eries of tetrahedral Zr-MOPs, the stabilities of which were systematicallys tudied at differentp Hv alues. All of these polyhedra exhibited excellent stabilityi na cidic, neutral, and even alkaline aqueous solution environments.…”
Section: Introductionmentioning
confidence: 99%
“…The different binding characteristics meet the essential requirement for fabrication of HDCCs through multiple orthogonal coordinative interactions. Our previous works showed that the “hard” trinuclear Zr IV cluster can selectively coordinate to carboxylic acids to construct a coordination tetrahedron . When H 2 bpydc is combined with zirconocene dichloride to form a coordination tetrahedron cage, the bipyridyl groups can at the same time orthogonally coordinate with other “soft” metal ions such as Cu II or Pd II , thus inducing the formation of a HDCC.…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, Liu et al. synthesized four Zr IV ‐based tetrahedral carboxylate cages with the molecular formula {[Cp 3 Zr 3 μ 3 ‐O(μ 2 ‐OH) 3 ] 4 (bdc) 6 } ⋅ Cl 4 ⋅ n S; {[Cp 3 Zr 3 μ 3 ‐O(μ 2 ‐OH) 3 ] 4 (btc) 4 } ⋅ Cl 4 ⋅ 4 DMF ⋅ n S; {[Cp 3 Zr 3 μ 3 ‐O(μ 2 ‐OH) 3 ] 4 (bpdc) 6 } ⋅ Cl 4 ⋅ n S; and {[Cp 3 Zr 3 μ 3 ‐O(μ 2 ‐OH) 3 ] 4 (btb) 4 } ⋅ Cl 4 ⋅ n S, in which Cp=cyclopentadienyl, bdc=benzene‐1,4‐dicarboxylate, btc=benzene‐1,3,5‐tricarboxylate, bpdc=4,4′‐biphenyldicarboxylate, H 3 btb=4,4′,4′′‐benzene‐1,3,5‐triyltris (benzoic acid), and S represents free solvent molecules . All these cationic cages are isostructural in nature.…”
Section: Design Strategies To Construct Stable Porous Carboxylate Mopsmentioning
confidence: 99%
“…[67] The NBO charge on Oa toms in OH À is higher than that of Oa toms in COOH groups (À1.403 vs. À0. 74 [68] All these cationic cages are isostructural in nature.I na nother report, the same group developed a pair of heterometal (Pd II or Cu II )-decorated Zr IV carboxylate based cationic tetrahedral cages:Z r-bpydc-MCl 2 (H 2 bpydc = 2,2-bipyridine-5,5-dicarboxylic acid;M= Cu 2 + or Pd 2 + ). [69] These cages were prepared by three synthetic strategies:p ost-synthetic metallization, as tepwise metalloligand approach, and a one-pot synthesis.…”
Section: Increasingmetal-ligand Bond Strengthmentioning
confidence: 99%